TSA : an expert system for solid waste transfer station. - Abd Manaf, Latifah; Goh, Pei Pei; Mohd Zukki, Nur Ilyana; Abu Samah, Mohd Armi (Canadian Center of Science and Education, 2008)
This paper presents the development of expert system to assist in the operation of solid waste transfer station. The knowledge based consists of a rule-based expert system for the diagnosis of site selection and problems of transfer station and subsequent identification of remedial control actions. Siting criteria are used to identifying and evaluating potential development sites. It is generally recognized that an expert system can cope with many of the common problems relative with the operation and site selection of solid waste transfer station. In this work an expert system is developed which supervises the site selection and problem of waste transfer station. The knowledge acquisition to develop this expert system involved an exhaustive literature review on waste transfer station operation plant and interviews with experienced plant operators. The development tool for this system is Kappa-PC.